Muscle phosphofructokinase deficiency. Biochemical and immunological studies of phosphofructokinase isozymes in muscle culture. - Davidson, M (1983)
Muscle cultures from three unrelated patients with muscle phosphofructokinase (PFK; EC 2.7.1.11) deficiency (Glycogenosis type VII; Tarui disease) had normal PFK activity and normal morphology. Chromatographic and immunological studies showed that normal muscle cultures express all three PFK subunits, M (muscle-type), L (liver-type), and P (platelet-type) and contain multiple homotetrameric and heterotetrameric isozymes. Muscle cultures from patients lack catalytically active M subunit-containing isozymes, but this is compensated for by the presence of P- and L-containing isozymes. Despite the lack of muscle-type PFK activity, presence of immunoreactive M subunit was demonstrable by indirect immunofluorescence, suggesting a mutation of the structural gene coding for the M-subunit of PFK.